2017
DOI: 10.4103/0976-3147.203836
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cerebral Microbleeds in Thai Patients with Ischemic Stroke

Abstract: Background:With the widespread use of magnetic resonance imaging (MRI), cerebral microbleeds (CMBs) are commonly detected. Ethnicity seems to play a role in the prevalence of CMB, with higher prevalence in participants from Asian origin. The purpose of the study is to look for the prevalence of CMBs and associated factors in Thai patients with ischemic stroke.Methods:Patients with acute ischemic stroke who had MRI and magnetic resonance angiography during January–August 2014 were included in the study. T2*-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…in their study (Prevalence of cerebral microbleeds in Thai patients with ischemic stroke) published in the current issue of this journal showed that the prevalence of CMBs was 20% in the Thai population which was never reported earlier. [ 3 ] This was lower than the Japanese cohort but was at par with the published Chinese prevalence. In their study, hypertension and small vessel disease on MRI especially Fazeka stage 3 related to hypertension was associated with increased risk for CMBs.…”
mentioning
confidence: 64%
“…in their study (Prevalence of cerebral microbleeds in Thai patients with ischemic stroke) published in the current issue of this journal showed that the prevalence of CMBs was 20% in the Thai population which was never reported earlier. [ 3 ] This was lower than the Japanese cohort but was at par with the published Chinese prevalence. In their study, hypertension and small vessel disease on MRI especially Fazeka stage 3 related to hypertension was associated with increased risk for CMBs.…”
mentioning
confidence: 64%
“…Potigumjon et al in their study (Prevalence of cerebral microbleeds in Thai patients with ischemic stroke) published in the current issue of this journal showed that the prevalence of CMBs was 20% in the Thai population which was never reported earlier. [3] This was lower than the Japanese cohort but was at par with the published Chinese prevalence. In their study, hypertension and small vessel disease on MRI especially Fazeka stage 3 related to hypertension was associated with increased risk for CMBs.…”
mentioning
confidence: 57%
“…Their effectiveness is comparable to that of warfarin, but the associated risk of a CH event is significantly lower than that of warfarin. Two small sample studies in Japan [4, 30] showed that NOACs do not increase the risk of new CMBs. Patients with AF and a high risk of embolism need long-term anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate of CMBs in people over 80 years old is as high as 35.7% [3]. The incidence of CMBs in ischemic stroke patients is approximately 20% [4]. Studies have shown that CMBs not only have an important impact on hemorrhagic transformation but are also an independent risk factor for new ischemic stroke or transient ischemic attack and stroke recurrence [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation